Analisis Kapabilitas Pemerintah Desa Dalam Melaksanakan Program Prioritas Pembangunan Desa Berdasarkan Undang-Undang Nomor 6 Tahun 2014 Tentang Desa - Gatot Budiarto (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2018)
A kind of activities that must be done by rural government is to maintain the village development. The village development is conceptually regulated in Law No. 6 of 2014 about the Villages. This study was based on the results of research on the evaluation of rural government in implementing village development priorities. This research was conducted in Payakabung Village, Indralaya Utara Sub-district, Ogan Ilir Regency. The main objective of the study was to know the extent of the conformity between the developments that has been implemented towards the ideal concept of village development in Law No. 6 of 2014 about the Village. The study used descriptive qualitative designs with individual analysis units consisting of the elements of rural government and local communities. The study used the concept of ex-post evaluation. The results of the study found that the implementation of priority programs of village development in Payakabung Village Ogan Ilir Regency has not been implemented optimally. From the five dimensions of village development under study, it is known that various problems arose in each of the dimensions of village development which showed the non-conformity towards the ideal concept of village development in the legislation. It highlights that the identified village development problems were the independence and weak village government's understanding of ideal village development, external factors beyond the control of the rural government, and the low level of community participation in some dimensions of village development.Â Â